The epidemiology of antimicrobial resistant bacterial infection in Qatar: A systematic review and meta-analysis - Rasha, Abu El-Ruz (2025)
BackgroundAntimicrobial resistance (AMR) is the current silent pandemic responsible for approximately five million deaths annually. According to the WHO, antimicrobial resistance is one of the top global public health threats and the third leading cause of death worldwide. MethodThis systematic review and meta-analyses aims to provide Qatar's first comprehensive epidemiological assessment of AMR. We conducted extensive search of three databases (PubMed, Embase and Web of Science) using broad search terms with no restrictions. The meta-analysis of prevalence was done using the Freeman-Turkey transformation and random effects models. Subgroup analysis was performed for three categories; the composite isolates, otherwise responsive isolates, and otherwise resistant isolates. ResultsThe search yielded a total of 1258 publications, of which 55 publications were included. The overall prevalence of all isolates was 13.64 % (95 %CI: 6.80 – 22.11, I2=99 %), all the studies were cross-sectional of convenience sampling, conducted in healthcare settings. The subgroup prevalence for the composite isolates was 8.87 % (95 %CI: 2.72 – 17.77, I2=98.7), otherwise responsive isolates was 11.37 % (95 %CI: 4.31 – 20.72, I2=98.3 %), otherwise resistant isolates was 23.55 % (95 %CI: 10.12 – 40.14, I2=99.1). The otherwise resistant isolates stratified analyses revealed that ESBL prevalence was 38.94 % (95 %CI: 21.63 – 57.79, I2=99.2 %), MDR was 15.99 % (95 %CI: 2.46 – 37.00, I2=99 %), MRSA was 52.37 % (95 %CI: 13.91 – 89.50, I2=88 %), Nosocomial infections prevalence was 23.55 % (95 %CI: 10.12 – 40.14, I2=98.2 %). The ESKAPE bacterial strains accounted for the majority of resistance. ConclusionQatar’s AMR overall prevalence is close to the global estimates, however the resistant isolates prevalence is higher than average according to the global estimates for high-income countries. The AMR public health response including national action plan to combat AMR and antimicrobial stewardship programs need to be orchestrated. AMR epidemiological research needs improvement in expanding coverage across diverse population groups to ensure greater clarity and precision in identifying bacterial infections and antibiotic classifications.